The Giving of Stunting Pocketbooks as a Health Education Tool for Women of Childbearing Age in an Effort to Prevent Stunting - S Sarliana; Henrietta Imelda Tondong; Mercy Joice Kaparang; Hastuti Usman (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Stunting is a chronic nutritional problem that can increase morbidity and mortality. Indonesia has a stunting rate of 24.4%, far from the government's target of 14% in 2024. Central Sulawesi Province is one of the regions with a high stunting rate (29.7%) and Enu Village contributes 41% as the stunting locus. Stunting prevention efforts must be carried out from an early age, especially for women of childbearing age as prospective brides and prospective mothers, who need to be equipped with good knowledge of stunting. This study aims to prove the effectiveness of giving a stunting pocketbook as a means of health education for women of childbearing age to prevent stunting. The research method used is a Pre-Experiment with one group pretest-posttest design. it was implemented in June 2022 in Enu Village, the working area of the Toaya Health Center. A sample of 36 people was taken using a purposive sampling technique, data analysis using univariate analysis and bivariate analysis using paired t-test. The results showed an increase in the average knowledge before and after treatment of 14.72 with p-value = 0.001. Giving a stunting pocketbook as an educational tool has proven to increase the knowledge of women of childbearing age. It is hoped that education with pocketbooks can be given to teenagers as one of the preventive efforts to reduce the incidence of stunting. Abstrak: Stunting merupakan masalah gizi kronis yang dapat meningkatkan angka kesakitan dan kematian. Indonesia angka kejadian stunting 24,4 %, jauh dari target pemerintah yaitu 14% pada tahun 2024. Provinsi Sulawesi Tengah menjadi salah satu wilayah dengan angka stunting tinggi (29,7 %) dan Desa Enu menyumbang 41% sebagai locus stunting pada wilayah kerja puskesmas Toaya. Upaya Pencegahan stunting harus dilakukan sejak dini khususnya bagi wanita usia subur sebagai calon pengantin dan calon ibu, perlu dibekali dengan pengetahuan yang baik terkait dengan stunting. Tujuan penelitian ini yaitu untuk membuktikan efektifitas pemberian buku saku stunting sebagai sarana edukasi kesehatan bagi wanita usia subur dalam upaya pencegahan stunting. Metode penelitian yang digunakan Pre-Experiment dengan rancangan one group pretest-posttest design. Dilaksanakan bulan Juni 2022 di Desa Enu wilayah kerja Puskesmas Toaya. Sampel sebanyak 36 orang diambil dengan tekhnik Purposive Sampling. Analisis data menggunakan analisis univariat dan bivariat menggunakan uji paired t test. Hasil menunjukan terdapat peningkatan rata-rata pengetahuan sebelum dan sesudah perlakuan sebesar 14,72 dengan nilai p-value = 0,001. Pemberian Buku saku stunting sebagai sarana edukasi terbukti efektif dalam meningkatkan pengetahuan wanita usia subur. Diharapkan edukasi dengan buku saku dapat diberikan kepada remaja sebagai salah satu upaya preventif menekan angka kejadian stunting.